Hypolipidemic constituents from the aerial portion of Sibiraea angustata. Issue 11 (1st June 2020) - Liu, Hongdong; Zhang, Ting; Jiang, Piao; Zhu, Weifeng; Yu, Songhua; Liu, Yong; Li, Bin; Li, Fei
Graphical abstract: Abstract: Two new monoterpene acylglucosides (1 –2 ) and one new aromatic glycoside (3 ), together with five known compounds (4 –8 ), were isolated from 95% ethanol extract of Sibiraea angustata . The structures of these compounds were characterized by 2D-NMR and mass spectrometry. Compounds were evaluated for their hypolipidemic activity using oleic acid-induced lipid accumulation in HepG2 cells. RT-PCR analysis revealed that compound 5 could decrease the expression level of fatty acid synthase (FASN). Lipidomics analysis indicated that compound 5 significantly decreased the levels of 11 lipids in oleic acid-induced lipid accumulation, including triglycerides (TG), diglycerides (DG), phosphatidylcholines (PC) and 1-acyl-sn-glycero-3-phosphocholines (lysoPC). These data demonstrated that terpene acylglucosides are the major active constituents in Sibiraea angustata .